Anemia in Pregnancy - Pandey, Nira (Journal of Nursing Education of Nepal, 2023)
Anemia is one of the most prevalent nutritional deficiency problems affecting pregnant  women. All pregnant women are at risk for becoming anemic that is because iron need for  mother and fetus gradually increases during pregnancy and reaches its highest level at the end  of the pregnancy. The most important cause of anemia during pregnancy is an inadequate of  iron, because diet alone is not sufficient to meet iron requirement during pregnancy. Anemia in  pregnancy is considered one of the major risk factors contributing to maternal morbidity and  mortality. That is why early diagnosis and treatment of anemia is very important in pregnant  women.
Keywords: Anemia; Pregnancy; Iron deficiency; Maternal morbidity; Maternal mortality